AKTYWNOŚĆ BEZROBOTNYCH W ŚWIETLE PSYCHOLOGICZNYCH MODELI POSZUKIWANIA PRACY - Chirkowska-Smolak, Teresa (Wydział Prawa i Administracji UAM, 2000)
Considerations of the Author are focused on conceptions relating to searching of a job by unemployed people as well as on an attempt to verify premises of respective models of job searching that were generated within the framework of social sciences. Against this background a dynamic process of job searching has been presented, seen as an adaptive strategy of overcoming the position of unemployed person. Such an activity is an action aimed at desired goal and its most important premise says that the value itself of this goal as well as expectation involved with reaching it are main factors of motivation towards adequate remedial measures or steps. Variants relating to personal character features and to situational facts first of all - do play an eminent role in undertaking such measures. The adoption of such an assumption enables us to overcome simplifications proper to economic models but also - limitations of the hitherto models as proposed on the ground of psychology.
ACTIVITY OF THE UNEMPLOYED IN THE LIGHT OF PSYCHOLOGICAL MODELS FOR JOB SEARCHING PROCESS